2018
DOI: 10.1002/ajh.25154
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of chemotherapy or chemo‐anti‐PD‐1 combination after failed anti‐PD‐1 therapy for relapsed and refractory hodgkin lymphoma: A series from lysa centers

Abstract: Anti-PD-1 therapy provides high response rates in Hodgkin lymphoma (HL) patients who have relapsed or are refractory (R/R) to autologous stem cell transplantation (ASCT) and brentuximab vedotin (BV), but median progression free survival (PFS) is only one year. The efficacy of treatment following anti-PD-1 is not well known. We retrospectively investigated the efficacy of salvage therapies for unsatisfactory response to anti-PD-1 therapy, assessed by PET-CT according to the Lugano criteria, in 30 R/R HL patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 28 publications
6
77
0
1
Order By: Relevance
“…(11) Second, recent reports suggested that anti PD-1 mAb could be discontinued in patients achieving complete metabolic response (31) and that more aggressive strategies (i.e., addition of chemotherapy, consolidation with allograft) may be required for patients who are unable to achieve a complete response. (32) The limitations of this study are the retrospective analysis of a multicenter population of patients with moderate sample size. First, the sample size is small compared to datasets evaluating standard of care drugs.…”
Section: Discussionmentioning
confidence: 99%
“…(11) Second, recent reports suggested that anti PD-1 mAb could be discontinued in patients achieving complete metabolic response (31) and that more aggressive strategies (i.e., addition of chemotherapy, consolidation with allograft) may be required for patients who are unable to achieve a complete response. (32) The limitations of this study are the retrospective analysis of a multicenter population of patients with moderate sample size. First, the sample size is small compared to datasets evaluating standard of care drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a rationale that DNA damaging agents are able to promote immunogenicity of cancer cells trough increasing neo‐antigen repertoire, inducing immunogenic cell death and changing the cytokine milieu into the tumor microenvironment, with a consequence redistribution and increase expression of PDL‐1 on tumor cells, good results are being achieved combining PD1 inhibitors with chemotherapy, both in solid tumors and in lymphomas setting 20‐24 . On the other side, patients who already failed anti‐PD1 therapy, seems to benefit from a re‐treatment with conventional CHT, leading to the idea that PD1 inhibitors can re‐sensitize tumor cells to conventional treatment, previously failed 12,13 . Rossi et al showed an overall response in 16 (67%) out of 30 R/R HL patients treated with conventional CHT after anti‐PD1 treatment (CR: 46%), regardless of whether patients had been re‐exposed to an agent to which they were previously resistant.…”
Section: Discussionmentioning
confidence: 99%
“…182 Besides evidence supporting the optimization of tumor response to PD1-blockade with the addition of hypomethylating agents, a retrospective trial of 30 patients with rr-cHL and unsatisfactory response to anti-PD1 therapy proposed the beneficial effect of previous checkpoint blockade on the following chemotherapy administration, either alone or in combination with the previous anti-PD1 agent, by demonstrating 61% and 90% objective response rates in the 'sequential' and 'combination' strategy, respectively. 183 Recently, Carreau and colleagues evaluated 77 heavily pretreated cHL patients who received a subsequent line of therapy after anti-PD1 blockade.…”
Section: Brentuximab Vedotin As Salvage Therapy For Relapsed/refractomentioning
confidence: 99%